Comparative study of different Sense Amplifiers in 0.18um technology - Kumar, Sunil; Chatterjee, Arun Kr. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
A comparative study of different types of sense amplifiers [1] using 0.18um technology is presented. The sense amplifiers under considerations are used in SRAM and DRAM cells.The sensing delay of different types of sense amplifiersÂ  are evaluated with respect to variation of bitline capacitance. Comparative results are also provided for the variation in delay with respect to power supply. Extensive results based on 0.18um CMOS technology using CADENCE Spectre simulation tools are presented for different architectures of sense amplifiers. From these results it has been proven that if the output of sense amplifier is isolated from the bitline parasitic capacitance then the sensing delay of sense amplifier reduces.